THE DECONSTRUCTION OF EDUCATIONAL VALUES IN THE MANGGARAI ETHNIC GOET IDEP IN FLORES BY YOSEPH NGADUT - Karolus Budiman Jama (LLDIKTI Wilayah X, 2021)
Each ethnic group has a unique and culturally based way of instilling educational values. The inculcation of this value can be through literary works, both in the form of stories and poetry. Poetry in Manggarai ethnic literature, known as go'et. Goet is a way of inheriting the value of education in the Manggarai ethnic group in Flores. Through goet, this ethnic group educates future generations to become useful and critical human beings. This paper raises one of the go'et idep works written by cultural observer Yoseph Ngadut. This research is classified as a qualitative descriptive study with the literature technique as a way of obtaining data. Poststructural is used as an approach in analyzing data. From the results of data analysis, it was obtained four categories of go'et idep texts as a paradigm of planting educational values. These four categories are findings in research. (1) The metaphor of hard objects as a form of planting educational values ​​is closely related to behaviorism learning theory. (2) Soft equipment metaphorized with animals as cognitive learning in cultivating educational values. (3) The third category is the class of constructivism in instilling educational values. The emphasis lies on change towards progress. (4) The category of criticism, Goet Idep sees the urgency of criticism in instilling educational values, so that critical humanism will emerge.